Lean Distribution untuk Minimasi Keterlambatan Pengiriman Produk Susu - Siregar, M Tirtana; Ayu, Ni Wayan (Sekolah Tinggi Manajemen Transportasi (STMT) Trisakti, 2018)
The aim of this research is to determine the causes of delays in the delivery of products to consumers. Big picture mapping will describe the product delivery process flow starting from receiving product delivery orders to the product delivery process carried out by a third party company. Process activity mapping is used to categorize activities into three categories, namely value added, necessary, value added, and non value added. Waste activity identification that occurs in the product delivery process is carried out with the seven waste method, which then causes the waste factors to be analyzed using a fishbone diagram. Lean distribution method is useful for analyzing waste factors as much as possible, so that continuous improvement can be implemented immediately.